2019
DOI: 10.1111/ajpy.12222
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological responses to facial expression of surprise, sadness, and disgust

Abstract: Objective: The aim of the present study was to evaluate psychophysiological responses to expressions of surprise, sadness, and disgust and the possible effect of the expresser's sex. Method: The startle reflex, the skin conductance response (SCR), and heart rate (HR) were recorded in 50 participants while they viewed male and female expressions of surprise, sadness, and disgust. Results: The results showed enhanced startle reflex potentiation and greater HR deceleration in response to disgust expressions and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…According to previous studies, the facial expressions of disgust elicit stronger activation of the defensive motivational system and the orientation response than the those of sadness (Gantiva et al, 2019). Therefore, it is expected that the associative context of faces will be more advantageous for the acquisition of disgusting connotations than sad connotations for new words.…”
mentioning
confidence: 97%
“…According to previous studies, the facial expressions of disgust elicit stronger activation of the defensive motivational system and the orientation response than the those of sadness (Gantiva et al, 2019). Therefore, it is expected that the associative context of faces will be more advantageous for the acquisition of disgusting connotations than sad connotations for new words.…”
mentioning
confidence: 97%
“…A previous study [45] also mentioned that cardiac acceleration or deceleration was due to individual differences. In another study [46] about the psychological responses to facial expression in which the image appears as a kind of sudden event, the heart rate decrease and startle reflexes increase indicated that the rising of attention response and preparation for fight-or-flight response of the SNS system.…”
Section: Discussionmentioning
confidence: 97%
“…For rodents, the magnitude of movements such as jumping are recorded using a load platform. For example, humans show larger startle responses when viewing or anticipating unpleasant pictures [26][27][28][29][30] or negative emotional expressions 31 , anticipating shock 32 , in the presence of odours previously paired with a stressful social experience 33 , and even when exposed to sweat odours from anxious donors 34 . In rodents, many studies demonstrate potentiated startle in subjects exposed to conditioned stimuli predicting an aversive event 25,28,[35][36][37][38] , an effect that may be mediated by corticotropin-releasing hormone 39 and attenuated by anxiolytic drugs (e.g.…”
mentioning
confidence: 99%